Strategi Peningkatan Mutu Layanan Kolaborasi Jaringan Transport Telekomunikasi di Indonesia - Saefurrohman, Asep; Hubeis, Musa; Mulyati, Heti (Jurnal Manajemen, 2022)
The study aims to analyze the factors that can improve service quality and formulate a strategy for improving the collaboration of telecommunication transportation network services at telecommunication companies in Indonesia. The method used in this study is an exploratory analysis based on the Information Technology Service Management (ITSM) framework and analysis of internal and external conditions as well as Analytical Hierarchy Process (AHP) calculations. Factors that can improve service quality are strategy, design, transition, operation, and Continual Service Improvement (CSI), while the preparation of service quality improvement strategies is accelerating the implementation of transport network roadmaps, developing resilience systems, forming agile teams and improving business processes. The results of the research can be used as a strategic proposal for improving the quality of transport network services in telecommunications companies.